Mucinous Pancreatic Cysts: Comparison of Cyst Size and Location in Certain Mucinous Cyst Subgroups - Köker, Ibrahim Hakki; Elagöz, Şahende; Gücin, Zuhal; Ümit Malya, Fatma; Şenturk, Hakan (Turkish Journal of Gastroenterology, 2021)
Background: There are studies reporting that the location of intraductal papillary mucinous neoplasia (IPMN) predicts malignancy. Therefore, we evaluated the cyst location’s relationship with malignancy, and the possibility of using cyst size and location to distinguish between non-main duct (non-MD)-IPMNs, mucinous cystic neoplasia (MCN), and cystic pancreatic ductal adenocarcinoma (PDAC). Methods: We performed a retrospective analysis of data from 122 patients with a definite cyto-histological diagnosis of non-MDIPMNs, LR-MCNs, and cystic PDACs via endoscopic ultrasound fine-needle aspiration between October 2011 and October 2020. We grouped the cyst locations as head, uncinate, neck (HUN), and corpus or tail (CT). On histology, low-grade dysplasia and intermediategrade dysplasia were considered low risk (LR), whereas high-grade dysplasia and invasive carcinoma were considered high risk (HR). Results: Of the 122 patients (61 (50%) women, median age 61.5 years (range 19-85), there were 34 (27.9%) LR-non-MD-IPMNs, 33 (27%) HR-non-MD-IPMNs, 19 (15.6%) LR-MCNs, and 36 (29.5%) cystic PDACs. We found no significant difference between LRand HR-non-MD-IPMN locations (P = .803). Low-risk non-MD-IPMNs were significantly smaller than HR-non-MD-IPMNs (P < .001), LR-MCNs (P = .002), and cystic PDACs (P < .001). The area under the receiver operating characteristic curve (AUROC) was 0.819 (95% CI: 0.716-0.902; P < .0001), and demonstrated a cyst size cut-off <2.2 cm to differentiate LR cysts, while cysts <1.6 cm had a negative predictive value (NPV) of 100% in non-MD-IPMNs. Conclusion: Cyst location is not predictive of malignancy in non-MD-IPMNs. Low-risk non-MD-IPMNs were smaller than HR-non-MDIPMNs, LR-MCNs, and cystic PDACs. The cyst size cut-off was 2.2 cm; however, <1.6 cm had a 100% NPV differentiating LR- from HR-non-MD-IPMNs.